Comparing signal to noise ratios of amplitude modulation following responses from four EEG derivations in awake normally hearing adults - van der Reijden, C S; Mens, L H; Snik, A F (Audiology, 2001)
Amplitude modulation following responses (AMFR) or steady-state evoked potentials (SSEPs) can be used for the objective and frequency-specific estimation of hearing thresholds in awake and sleeping subjects. To be useful as a clinical tool, a high signal to noise ratio (SNR) is required for a minimal testing time. Four EEG derivations were compared in six relaxed, cooperative awake normally hearing adults to compare the SNRs. Stimuli comprised a 1 kHz carrier wave, amplitude modulated at 39 Hz and 90 Hz. They were presented for about 4.4 min in one ear at a level slightly above the behavioural threshold (10 dB SL). In the 39 Hz condition, the SNRs from the different derivations did not differ significantly. However, in the 90 Hz condition one novel derivation (Cz-inion with ground at Pz) yielded a significantly lower noise level, about 60 per cent of the noise level of the other derivations. The SNR of this derivation was about 50 per cent larger than from other derivations. Such an increase of the SNR implies that testing time is reduced by about 56 per cent as compared to conventional derivations in these subjects.